Exploring Factors Influencing Consumer Purchase Decisions: A Study on UMKM Junior Baby: Pengaruh Kualitas Produk, Harga, dan Citra Merek terhadap Keputusan Pembelian Konsumen: Studi pada UMKM Junior Baby - Reza Nanda Tribianti; Asat Rizal (Universitas Muhammadiyah Sidoarjo, 2022)
This study examines the influence of product quality, price, and brand image on consumer purchase decisions in UMKM Junior Baby. Using quantitative methods and primary data, this research collected responses from 90 customers in Sidoarjo, Indonesia. Multiple linear regression analysis was employed to analyze the data with SPSS version 18. The results indicate that product quality, price, and brand image collectively exert a significant influence on consumer purchase decisions. Enhanced product quality, appropriate pricing, and a positive brand image positively affect consumers' willingness to make purchases. These findings contribute to understanding the factors that drive consumer behavior in the context of UMKM Junior Baby and have implications for practitioners seeking to optimize their marketing strategies. Highlights: Product quality: The study examines the impact of product quality on consumer purchase decisions, emphasizing the importance of delivering high-quality products to enhance customer satisfaction and drive sales. Price: The research investigates the influence of pricing strategies on consumer purchase decisions, highlighting the significance of offering competitive prices that align with product value to attract and retain customers. Brand image: The study explores the role of brand image in shaping consumer purchase decisions, emphasizing the need for UMKM Junior Baby to establish a positive and recognizable brand identity that resonates with their target market. Keywords: product quality, price, brand image, purchase decisions, UMKM Junior Baby